The National River Linking Project [NRLP] of India: some contentious issues. - Amarasinghe, Upali A. (International Water Management Institute, 2012)
India's National River Linking Project (NRLP), which has been on the drawing board for some three decades, is the largest inter-basin water transfer planned to date in India or elsewhere. The idea has waxed and waned depending upon the political dispensation at any given point in time. Under the Challenge Program for Water and Food, IWMI undertook a broad strategic exploration of the basic idea of NRLP and its assumptions. This Highlight examines few contentious issues of the NRLP that received considerable attention in the national discourse. And it concludes that the donor basins may have surplus water to make NRLP technically feasible; however, there is need for nuanced analysis of whether, as the best possible option available to India, it is justifiable.